Of Sky, Water and Skin: Photographs from a Zanzibari Darkroom - Gupta, Pamila (Kronos: Southern African Histories, 2021)
In this article, I propose to take up the concept and physical space of a photographic ‘darkroom’ located in Stone Town, Zanzibar, to explore a set of images from the Capital Art Studio (1930–present) collection produced by Ranchhod Oza (1907– 93), and inherited by his son Rohit Oza (1950–). I employ a concept of darkness to read this visual archive differently and propose multiple ‘other lives’ for a set of images. First, by bringing this African photography collection to light, I am taking it out of the ‘dark rooms’ of history in one sense and exposing it for interpretation. Second, I focus my lens on the Oza physical darkroom located in the back of the studio on Kenyatta Road in Stone Town, where photographs of a range of Zanzibari persons were both developed and printed and that open up the darkroom as a place of photographic complexity and sensorium, and not just mechanical reproduction. Third, I develop darkness as a form of beauty in certain images of sky, water and skin from this archive that showcase Zanzibar’s position as an Indian Ocean island and port city whilst under rule by the Omani Sultanate (1698–1964) and British Protectorate (1890–1963). Fourth, I conceptualise the Zanzibar Revolution of 1964 as a time of visual darkness, which temporarily restricted photographic practices operating in Stone Town under the new Afro-Shirazi political party. Throughoutmy analysis, I use a framing of ‘darkness’ to interrogate photography as an aesthetic practice deeply immersed in materialities and metaphors of dark and light, black and white, and as integral to Zanzibar’s oceanic islandness.